Computational design of organometallic oligomers featuring 1, 3‐metal‐carbon bonding and planar tetracoordinate carbon atoms. Issue 2 (24th September 2015) - Zhao, Xue‐Feng; Yuan, Cai‐Xia; Wang, Xiang; Li, Jia‐Jia; Wu, Yan‐Bo; Wang, Xiaotai
Abstract : Density functional theory computations (B3LYP) have been used to explore the chemistry of titanium–aromatic carbon "edge complexes" with 1, 3‐metal‐carbon (1, 3‐MC) bonding between Ti and planar tetracoordinate Cβ . The titanium‐coordinated, end‐capping chlorides are replaced with OH or SH groups to afford two series of difunctional monomers that can undergo condensation to form oxide‐ and sulfide‐bridged oligomers. The sulfide‐linked oligomers have less molecular strain and are more exergonic than the corresponding oxide‐linked oligomers. The HOMO–LUMO gap of the oligomers varies with their composition and decreases with growing oligomer chain. This theoretical study is intended to enrich 1, 3‐MC bonding and planar tetracoordinate carbon chemistry and provide interesting ideas to experimentalists. Organometallic complexes with the TiE2 (E = OH and SH) decoration on the edge of aromatic hydrocarbons have been computationally designed, which feature 1, 3‐metal‐carbon (1, 3‐MC) bonding between titanium and planar tetracoordinate β‐carbon. Condensation of these difunctional monomers by eliminating small molecules (H2 O and H2 S) produce chain‐like oligomers. The HOMO–LUMO gaps of the oligomers decreases with growing oligomer chain, a trend that suggests possible semiconductor properties for oligomers with longer chains. © 2015 Wiley Periodicals, Inc. Abstract : Organometallic complexes with the TiE2 (E=OH and SH) decoration on the edge of aromatic hydrocarbons have been computationally designed, which feature 1, 3‐metal‐carbon (1, 3‐MC) bonding between titanium and planar tetracoordinate β‐carbon. Condensation of these di‐functional monomers by eliminating small molecules (H2 O and H2 S) produce chain‐like oligomers. The HOMO‐LUMO gaps of the oligomers decreases with growing oligomer chain, a trend that suggests possible semi‐conductor properties for oligomers with longer chains.